Efficient heat extraction from the storage zone of solar pond by structurally improved spiral pipes; numerical simulation/experimental validation. (November 2022) - Hashemian, Mehran; Jafarmadar, Samad; El-Shorbagy, M.A.; Rahman, Anas A.; Dahari, Mahidzal; Wae-hayee, Makatar
Abstract: Various semi-O/O-shape dimple patterns were applied on the flat spiral pipes as a regional contorting policy. In this method only the critical regions that may cause significant effect on the improvement of the hydrothermal performance can be subjected to structural modification. The all-round geometrical modifications causes excessive pressure drop while this method can solve this problem to some extent. Archimedean spiral geometry of spiral pipe makes uneven hydraulic-thermal characteristics along the pipe, so regional geometrical modification allows to pinpoint the optimal model. Using semi-O or O-shape dimples or combination of both on the inner or outer (or on both wall) leads to obtain unique cases. Constant wall temperature of 360 K was applied for the outer wall of all cases to evaluate the strength of each case based on heat extraction potential. The effect of arrangement, position, and type of dimples was taken under consideration. To get elaborate comprehension about the frictional and thermal behavior of each design, several criteria including Nusselt number (Nu), friction factor (f), thermal performance factor (TPF), temperature efficiency ( ɛ ), and J-factor were employed. Moreover, the effect of flow inlet position on the said was explored. All investigations were done in the flow velocity range of 0.1–0.6 m/s. The findings showed that case "c" (spiral pipe with dimples on the inner wall) has the highest heat extraction potential and improves heat extraction by 27% compared to the smooth spiral pipe. Also, case "c" makes the lowest pressure drop. Hence, by owning said two positive features case "c" provided the highest TPF, ɛ, and J-factor. Heat transfer improves when flow enters from the innermost turn. Graphical abstract: